2020
DOI: 10.29240/ef.v4i1.1158
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Reading Newspaper and Short Stories on Students’ Vocabulary Size at Cenderawasih University Setting

Abstract: This study aimed to investigating the effect of reading newspapers and short stories on students' vocabulary size and whether there is a significant difference between students who read newspapers and short stories at third semester of English Education Study Program in Cenderawasih University. The method of the research was quasi-experimental.  The sample of the research was the students of third semester English Education Study Program at Cenderawasih University. It consisted of 36 students who were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In getting ready the students for having proper capacity in reading, teachers are demanded to be innovative in using the variety of ways in teaching reading (Wijayanti, 2020). One of them is instructional reading materials.…”
Section: Instructional Reading Materialsmentioning
confidence: 99%
“…In getting ready the students for having proper capacity in reading, teachers are demanded to be innovative in using the variety of ways in teaching reading (Wijayanti, 2020). One of them is instructional reading materials.…”
Section: Instructional Reading Materialsmentioning
confidence: 99%
“…The majority (90%) of research focusing on the effectiveness of short stories use to build vocabulary revealed that short stories facilitated significantly better results in vocabulary development than the use of other materials or tools administered to the control groups. Wijayanti (2020) is the only research reporting that short story use had no significant difference with the use of the materials provided to the control group. She found that both short stories and newspaper readings significantly increased students' vocabulary size, but there was no significant difference between the short stories and newspaper groups.…”
Section: Rq4: What Are the Results Of The Research?mentioning
confidence: 94%
“…Indeed, only 94% of the research revealed that the experimental group outperformed the control group. The other 6% (Kim, 2018;Wijayanti, 2020) showed the experimental group and the control group had no significant difference. Yet, the independent variables of both experimental and control groups in these two research caused a significant increase each dependent variable.…”
Section: Rq4: What Are the Results Of The Research?mentioning
confidence: 96%
“…The first component is often considered as important yet problematic element. Vocabulary is a crucial element for mastering English skills (Dakhi & Fitria, 2019;Hikmah et al, 2022;Ledy et al, 2023;Wijayanti, 2020;Wulandari, 2021). Vocabulary helps someone to express their ideas in communicating with others (Al Adzillina & Hasanah, 2021;Wulandari, 2021).…”
Section: Introductionmentioning
confidence: 99%